Injury-Induced Accumulation of Glial Cell Line-Derived Neurotrophic Factor in the Rostral Part of the Injured Rat Spinal Cord - Hara, Takuya (Molecular Diversity Preservation International (MDPI), 2012)
The spinal cord of a 7-week-old female Wistar rat was hemi-transected at thoracic position 10 with a razor blade, and changes in glial cell line-derived neurotrophic factor (GDNF) protein and mRNA expression levels in the spinal cord were examined. GDNF protein and mRNA expression levels were evaluated by enzyme immunoassay and reverse transcription polymerase chain reaction, respectively. Although GDNF is distributed in the healthy spinal cord from 150 to 400 pg/g tissue in a regionally dependent manner, hemi-transection (left side) of the spinal cord caused a rapid increase in GDNF content in the ipsilateral rostral but not in the caudal part of the spinal cord. On the other hand, injury-induced GDNF mRNA was distributed limitedly in both rostral and caudal stumps. These observations suggest the possibility that increased GDNF in the rostral part is responsible for the accumulation of GDNF that may be constitutively transported from the rostral to caudal side within the spinal cord. Although such local increase of endogenous GDNF protein may not be sufficient for nerve regeneration and locomotor improvement, it may play a physiological role in supporting spinal neurons including motoneurons.